Anti-Human Immunodeficiency Virus-1 Property of Thai Herbal Extract Kerra™ - Siriwan Saehlee; Supaphorn Seetaha; Wiwat Klankaew; Pussadee Srathong; Kiattawee Choowongkomon; Khuanjarat Choengpanya (MDPI AG, 2024)
Kerra™, a Thai traditional herbal medicine derived from the "Tak-Ka-Si-La Scripture" and composed of nine medicinal plants, has demonstrated potential antiviral properties against HIV. This study investigated the inhibitory effects of Kerra™ on HIV-1 reverse transcriptase (RT) and its ability to prevent pseudo-HIV viral infection in HEK293 cells. The results showed that Kerra™ extract achieved a 95.73 ± 4.24% relative inhibition of HIV-1 RT, with an IC50 value of 42.66 ± 8.74 µg/mL. Docking studies revealed that key phytochemicals in Kerra™, such as oleamide, formononetin, and biochanin A, interact with several residues in the RT non-nucleoside binding pocket, contributing to their inhibitory effects. Furthermore, Kerra™ was able to reduce pseudo-HIV infection in HEK293 cells at a concentration of 10 µg/mL, suggesting its potential as a supplementary treatment for HIV.